Copy Number Variants and Genetic Polymorphisms in TBX21, GATA3, Rorc, Foxp3 and Susceptibility to Behcet's Disease and Vogt-Koyanagi-Harada Syndrome - Liao, Dan (Sci Rep, 2015)
This study aimed to investigate the role of genetic variants including single nucleotide polymorphisms (SNPs) and copy number variants (CNVs) of TBX21, GATA3, Rorc and Foxp3 genes in Behcet's disease (BD) and Vogt-Koyanagi-Harada (VKH) syndrome in a Chinese Han population. Genotyping of 25 SNPs was performed by iPLEX system (Sequenom) or polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). TaqMan real time PCR was used to assess CNVs. The expression of Rorc and Foxp3 were examined by real-time PCR and cytokine production was measured by ELISA. High Rorc CNV was associated with the susceptibility to BD (P = 8.99 × 10(−8), OR = 3.0), and low Foxp3 CNV predisposed to BD in female patients (P = 1.92 × 10(−5), OR = 3.1). CNVs for the investigated genes were not altered in VKH syndrome. Further functional studies demonstrated that the relative mRNA expression levels of Rorc were increased in individuals with high Rorc copy number, but not for Foxp3. Increased production of IL-1β and IL-6 was found in individuals carrying a high CNV of Rorc. Our study showed that high CNVs of Rorc and low CNVs of Foxp3 confer risk for BD but not for VKH syndrome. The tested 25 SNPs in TBX21, GATA3, Rorc and Foxp3 did not associate with BD and VKH syndrome.